PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI TAHUN 2013-2015 - Fermadi, Heru Lian; ', Makhdalena; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research on the financial performance and firm value has been carried out by researchers, but the results have not been consistent. Thus researchers are interested in studying the financial performance of firm value. The purpose of this study was to examine and analyze the effect of financial performance to firm value. The population of this research are the manufacturing companies listed in the Indonesia Stock Exchange that have complete data on return on assets, return on equity, and firm value for three consecutive years (2013-2015). Data type of variable of this research is secondary data obtained with techniques derived from Indonesia Stock Exchange website (www.idx.co.id). Data analysis in this research is using regression. The results showed that simultaneously ROA and ROE affect the firm value, but partially only the ROE that has an influence on firm value.Keywords: ROA, ROE, PBV